2021
DOI: 10.1186/s12944-021-01593-8
|View full text |Cite
|
Sign up to set email alerts
|

How cancer cells remodel lipid metabolism: strategies targeting transcription factors

Abstract: Reprogramming of lipid metabolism has received increasing recognition as a hallmark of cancer cells because lipid dysregulation and the alteration of related enzyme profiles are closely correlated with oncogenic signals and malignant phenotypes, such as metastasis and therapeutic resistance. In this review, we describe recent findings that support the importance of lipids, as well as the transcription factors involved in cancer lipid metabolism. With recent advances in transcription factor analysis, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 241 publications
(245 reference statements)
0
21
0
Order By: Relevance
“…Indeed, due to their high proliferation rate, cancer cells depend upon a large amount of metabolic energy to synthesize cellular membranes. 42 Lipids in cancer cells are therefore the main fuel source for membrane synthesis and become one of the major actors in tumor cells growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, due to their high proliferation rate, cancer cells depend upon a large amount of metabolic energy to synthesize cellular membranes. 42 Lipids in cancer cells are therefore the main fuel source for membrane synthesis and become one of the major actors in tumor cells growth.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the anti-liver metastatic effects of CGX in the present study, we anticipated that the modulation of hepatic lipid profiles might contribute to the reduction of colon-liver metastasis ( Figures 3 , 4 ). Tumor cells require an aberrantly high supply of energy from carbohydrates and lipids for fast growth; therefore, alteration of lipid contents and metabolism is considered one of the hallmarks of tumors ( Beloribi-Djefaflia et al, 2016 ; Jeong et al, 2021 ). Recent studies have showed that hepatic lipids promote liver metastasis via excessive increased metabolism in tumor cells ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids serve a plethora of roles in human metabolism (226), acting as: cell membrane constituents, signaling molecules, energy supply, and energy storage. Changes in lipid concentrations have been reported in various types of cancer (227)(228)(229)(230)(231)(232)(233) and lipid metabolic reprogramming has become a hallmark of cancer (228,233).…”
Section: Overall View On Lipid Analysismentioning
confidence: 99%